Pains of Imprisonment Beyond Prison Walls: Qualitative Research With Females Labelled as Not Criminally Responsible - Mertens, Anouk (International journal of offender therapy and comparative criminology, 2020)
Research on the importation and deprivation models has focused almost exclusively on male inmates, and these models have not yet been studied in any setting other than prison. This research explores the importation and deprivation experiences of females labelled as not criminally responsible (FNCR). During the first part of the study, all the participants interviewed were in prison (n = 51). Follow-up interviews were carried out 18 months later, and while some participants were still in prison, others had been moved to (forensic or general) care. At that point, the study transcended the prison walls and extended its theoretical framework to forensic and general care facilities. In conclusion, the importation and deprivation framework, and the pains defined by Crewe, can be applied to FNCR in different types of setting. Most women were strongly affected by deprivations in prisons and in forensic care. Participants in forensic care sometimes felt more deprived than those in prison facilities.